The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1080/00365540500532860
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated nocardiosis due to unusual species: Two case reports

Abstract: Pulmonary nocardiosis is the major clinical manifestation of human nocardiosis and disseminated infection can be seen in immunocompromised patients. N. asteroides is the predominant pathogen associated with disseminated diseases. We report 2 cases of pulmonary nocardiosis admitted with disseminated infection, caused by rare species of Nocardia: Nocardia transvalensis and Nocardia cyriacigeorgica.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…This is an important point to clarify because it would mean that, at least in the southern United States, N. cyriacigeorgica is the most important cause of nocardiosis (5). The fact that N. cyriacigeorgica has been identified in Canada (11) and now in the northeastern United States with this report suggests that N. cyriacigeorgica might actually be distributed across all of North America, in addition to Europe and Asia (1,3,7,11,17,18,22,27,35). Clearly, N. cyriacigeorgica is a species that requires closer attention, and clinical microbiology laboratories need to adapt laboratory protocols for its specific identification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is an important point to clarify because it would mean that, at least in the southern United States, N. cyriacigeorgica is the most important cause of nocardiosis (5). The fact that N. cyriacigeorgica has been identified in Canada (11) and now in the northeastern United States with this report suggests that N. cyriacigeorgica might actually be distributed across all of North America, in addition to Europe and Asia (1,3,7,11,17,18,22,27,35). Clearly, N. cyriacigeorgica is a species that requires closer attention, and clinical microbiology laboratories need to adapt laboratory protocols for its specific identification.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews of collections of Nocardia clinical isolates by genotypic methods have found that a significant proportion, originally identified by routine phenotypic and chemotaxonomic methods, belong to a new species, Nocardia cyriacigeorgica (18,27,29,35). This species was first described in 2001 (38), and strains of N. cyriacigeorgica have since been recovered as the etiologic agent of human infection in Western Europe, Greece, Turkey, Japan, Thailand, and Canada (1,3,6,7,11,17,18,22,27,35,39). Most cases of infection have occurred in the context of human immunodeficiency virus-related or iatrogenic immune suppression.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 In addition, isolates of N. cyriacigeorgica have been identified by 16S r RNA gene sequence analysis from patients with disseminated disease in Canada, France, Greece and The Netherlands. [9][10][11][12][13] In these paper we described a pneumonia case in which N. cyriacigeorgica is causative agent.…”
Section: A Case Of Pulmonary Nocardiosis Due Tomentioning
confidence: 99%
“…Using sequence analysis, an additional study of 121 isolates identified as "N. asteroides" from Japan and Thailand showed 27 of these isolates (22.3%) to have 16S rRNA gene sequences identical to that of the type strain of N. cyriacigeorgica. In addition, isolates of N. cyriacigeorgica have been identified by 16S rRNA gene sequence analysis from patients with disseminated disease in Canada, France, Greece, The Netherlands, and Turkey (1,2,11,14,21).…”
mentioning
confidence: 99%